Representation of the image of a political leader in men in the modern Kazakh society - Kapbasova, G.B.; Kervalishvili, R. (KSU Publ., 2015)
The article deals with the quality of political leadership in this regard, the study was conducted in two phases. In the first phase analyzed the media, with which words were allocated category characterizing the image of a political leader. In the second phase, also with a view to identifying image of the political leader of the study were performed on 2 samples of male subjects: indigenous migrants from Kazakhstan and Georgia. It was found that ethnic and cultural stereotypes have a significant impact on the formation of an image of the future in our subjects. But on the political representation of these factors have a significant impact.
Қазіргі қазақстандық қоғамындағы ерлердің саяси көшбасшы кейіпі туралы түсінік
Представления об образе политического лидера у мужчин в современном казахстанском обществе
Keywords: image of the future; psychology migration; presentation of the image of a political leader